Conversion of individuals at risk for spinocerebellar ataxia types 1, 2, 3, and 6 to manifest ataxia (RISCA): a longitudinal cohort study. Issue 9 (September 2020) - Jacobi, Heike; du Montcel, Sophie Tezenas; Romanzetti, Sandro; Harmuth, Florian; Mariotti, Caterina; Nanetti, Lorenzo; Rakowicz, Maria; Makowicz, Grzegorz; Durr, Alexandra; Monin, Marie-Lorraine; Filla, Alessandro; Roca, Alessandro; et al.
Summary: Background: Spinocerebellar ataxias (SCAs) are autosomal dominant neurodegenerative diseases. Our aim was to study the conversion to manifest ataxia among apparently healthy carriers of mutations associated with the most common SCAs (SCA1, SCA2, SCA3, and SCA6), and the sensitivity of clinical and functional measures to detect change in these individuals. Methods: In this prospective, longitudinal, observational cohort study, based at 14 referral centres in seven European countries, we enrolled children or siblings of patients with SCA1, SCA2, SCA3, or SCA6. Eligible individuals were those without ataxia, defined by a score on the Scale for the Assessment and Rating of Ataxia (SARA) of less than 3; participants had to be aged 18–50 years for children or siblings of patients with SCA1, SCA2, or SCA3, and 35–70 years for children or siblings of patients with SCA6. Study visits took place at recruitment and after 2, 4, and 6 years (plus or minus 3 months). We did genetic testing to identify mutation carriers, with results concealed to the participant and clinical investigator. We assessed patients with clinical scales, questionnaires of patient-reported outcome measures, a rating of the examiner's confidence of presence of ataxia, and performance-based coordination tests. Conversion to ataxia was defined by an SARA score of 3 or higher. We analysed the association of factors at baseline with conversion to ataxia and the evolution of outcome parameters on temporal scales (time from inclusion and time to predicted age at ataxia onset) in the context of mutation status and conversion status. This study is registered with ClinicalTrials.gov, NCT01037777 . Findings: Between Sept 13, 2008, and Oct 28, 2015, 302 participants were enrolled. We analysed data for 252 participants with at least one follow-up visit. 83 (33%) participants were from families affected by SCA1, 99 (39%) by SCA2, 46 (18%) by SCA3, and 24 (10%) by SCA6. In participants who carried SCA mutations, 26 (52%) of 50 SCA1 carriers, 22 (59%) of 37 SCA2 carriers, 11 (42%) of 26 SCA3 carriers, and two (13%) of 15 SCA6 carriers converted to ataxia. One (3%) of 33 SCA1 non-carriers and one (2%) of 62 SCA2 non-carriers converted to ataxia. Owing to the small number of people who met our criteria for ataxia, subsequent analyses could not be done in carriers of the SCA6 mutation. Baseline factors associated with conversion were age (hazard ratio 1·13 [95% CI 1·03–1·24]; p=0·011), CAG repeat length (1·25 [1·11–1·41]; p=0·0002), and ataxia confidence rating (1·72 [1·23–2·41]; p=0·0015) for SCA1; age (1·08 [1·02–1·14]; p=0·0077) and CAG repeat length (1·65 [1·27–2·13]; p=0·0001) for SCA2; and age (1·27 [1·09–1·50]; p=0·0031), confidence rating (2·60 [1·23–5·47]; p=0·012), and double vision (14·83 [2·15–102·44]; p=0·0063) for SCA3. From the time of inclusion, the SARA scores of SCA1, SCA2, and SCA3 mutation carriers increased, whereas they remained stable in non-carriers. On a timescale defined by the predicted time of ataxia onset, SARA progression in SCA1, SCA2, and SCA3 mutation carriers was non-linear, with marginal progression before ataxia and increasing progression after ataxia onset. Interpretation: Our study provides quantitative data on the conversion of non-ataxic SCA1, SCA2, and SCA3 mutation carriers to manifest ataxia. Our data could prove useful for the design of preventive trials aimed at delaying the onset of ataxia by aiding sample size calculations and stratification of study participants. Funding: European Research Area Network for Research Programmes on Rare Diseases, Polish Ministry of Science and Higher Education, Italian Ministry of Health, European Community's Seventh Framework Programme.